PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DENGAN INTELLECTUAL CAPITAL DISCLOSURE SEBAGAI VARIABEL PEMODERASI (Studi Pada Perusahaan Manufaktur Di BEI Tahun 2016-2019) - Evinda Sari Tumangger; Rapel Rapel; Ferry Christian (Universitas Palangka Raya, 2023)
The value of the company is the investor's perception of the success rate of the company which is often associated with the share price. The high share price makes the company's value high and increases market confidence. The purpose of this research is to determine the influence of Good Corporate Governance on The Company's Value with Intellectual Capital Disclosure as a Moderating Variable. Samples in this study as many as 32 companies with sampling techniques used is Purposive sampling. Data source obtained from IDX in the form of annual report. While the data analysis technique used is moderated regression analysis technique. The results showed that the influence of Good Corporate Governance on The Company's Value is not divided. Intellectual Capital Disclosure weakens the influence of Good Corporate Governance on the Company's Value in Manufacturing Companieslocated in IDX